Formulation of Mouthwash for Gingivitis from Combination Infusion of Salam leaves (Eugenia Polyantha Wight) and Betel leaf (Piper betle. L) - Putri, Megananda Hiranya; Julaeha, Euis; Herijulianti, Eliza; Nurjanah, Neneng (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Gingivitis is inflammation of the gingiva associated with bacterial activity in dental plaque. The combination of bay leaves and betel leaves infusion has been used as a toothbrush disinfectant. The purpose of this study was to obtain a stable and effective mouthwash formulation from the combination of both infusions to prevent and relieve gingivitis. Methods: Five mouthwash formulas were made by mixing the active ingredients which is a combination of bay leaves and betel leaves infusion, with additives. The combination namely F-I (100% : 0%); F-II (75% : 25%); F-III (50% : 50%); F-IV (25% : 75%) and F-V (0%: 100%). Antibacterial activity tests against Streptococcus mutans, Streptococcus sanguis, and Porphyromonas gingivalis and physical stability tests were carried out. Stability test was carried out by storing the formula at room temperature (280C), hot temperature (400C) and cold temperature (40C) for 3 storage cycles (6 weeks) and observing changes in the physical indicators of the solution, namely pH, specific gravity, viscosity and organoleptic conditions, namely homogeneity, clarity, color, aroma and taste at the end of every 2nd week. Results: F-I to F-V had no inhibitory activity against Streptococcus mutans and Streptococcus sanguis, but had inhibitory activity against Porphyromonas gingivalis in the range (7.19±0.48) to (8.29 ±0.82) mm (ANOVA with a significance value of 0.237 > 0.05).  The 5 formulas were more stable at cold storage, with organoleptic observations at the end of the 3rd cycle showing a slight precipitate (+), clear solution, light brown color, mint aroma and sweet taste. F-II formulas showed better physical indicators values because they were closer to the standard values. Conclusion:  The F-II formula is recommended as a mouthwash for gingivitis because significant for antibacterial effect and showed better physical indicators values as the standard values for herbal medicines.Keywords: antibacterial activity; bay leaves - betel leaves infusion; gingivitis; mouthwash formulation.